2012
DOI: 10.1155/2012/869753
|View full text |Cite
|
Sign up to set email alerts
|

Concentrating PV/T Hybrid System for Simultaneous Electricity and Usable Heat Generation: A Review

Abstract: Photovoltaic (PV) power generation is one of the attractive choices for efficient utilization of solar energy. Considering that the efficiency and cost of PV cells cannot be significantly improved in near future, a relatively cheap concentrator to replace part of the expensive solar cells could be used. The photovoltaic thermal hybrid system (PV/T), combining active cooling with thermal electricity and providing both electricity and usable heat, can enhance the total efficiency of the system with reduced cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…The U-pipe avoids the temperature gradient on the whole absorber and on every block cell and simultaneously produces electricity using the same temperatures. More recently, Zhang et al [142] proposed a PV system with integrated CPC plate that adopts a low precision solar tracking method; the performance can be better than the fixed installation or the case with periodic adjustment only in several months.…”
Section: Recent Developments In Concentrator-type Designmentioning
confidence: 99%
“…The U-pipe avoids the temperature gradient on the whole absorber and on every block cell and simultaneously produces electricity using the same temperatures. More recently, Zhang et al [142] proposed a PV system with integrated CPC plate that adopts a low precision solar tracking method; the performance can be better than the fixed installation or the case with periodic adjustment only in several months.…”
Section: Recent Developments In Concentrator-type Designmentioning
confidence: 99%
“…The WHR and SBS CPVT systems have been developed since 1970s and 1980s [18], respectively, and they have been reviewed in several documents [18][19][20][21][22][23][24][25][26][27][28][29][30][31]. However, most of these papers mainly concern the examinations of flat-plate PVT systems, and discussions on CPVT systems are not quite profound and comprehensive.…”
Section: Introductionmentioning
confidence: 99%
“…Several review articles on PVT technology [2][3][4][5][6][7][8][9][10]230,231,[297][298][299][300] and CPV technology [11][12][13][14][15][16][17] already exist in the literature. One review article on low-concentration CPVTs [232] is found in the literature. However, the article's main focus is primarily on discussing and reviewing CPVs, PVTs, cooling of PVs, effect of nonuniform illumination on PVs, and beam splitting systems with few CPVT systems briefly reviewed.…”
Section: Introductionmentioning
confidence: 99%